Emergency Department Management of Pediatric Unprovoked Seizures and Status Epilepticus in the State of Illinois. (October 2015) - Taylor, Connie; Piantino, Juan; Hageman, Joseph; Lyons, Evelyn; Janies, Kathryn; Leonard, Daniel; Kelley, Kent; Fuchs, Susan
The purpose of this survey and record review was to characterize emergency department management of unprovoked seizures and status epilepticus in children in Illinois. The survey was sent to 119 participating emergency departments in the Emergency Medical Services for Children program; responses were received from 103 (88% response rate). Only 44% of the emergency departments had a documented protocol for seizure management. Only 12% of emergency departments had child neurology consultation available at all times. Record review showed that 58% of patients were discharged home, 26% were transferred to another institution, and 10% were admitted to a non-intensive care unit setting. Ninety percent of patients were treated with anticonvulsants. Seizure education was provided by the primary emergency department nurse (97%) and the treating physician (79%). This project demonstrated strengths and weaknesses in the current management of pediatric seizure patients in Illinois emergency departments.